Pengaruh Jenis Gula dan Waktu Fermentasi Terhadap Kualitas Minuman Fermentasi Kombucha Air Kelapa - Sipahutar, Alin Syafira; Elwina, Elwina; Zulkifli, Zulkifli (Jurnal Riset, Inovasi, Teknologi & Terapan, 2024)
Coconut water is rich in nutrients in the form of sugar, protein, fat, electrolytes, growth hormones and is relatively good for developing bacterial growth to produce other food products. As a diversification of coconut water waste, coconut water is processed into a fermented coconut water kombucha drink. This research aims to determine the effect of the type of sugar and fermentation time on the quality of the fermented coconut water kombucha drink by varying the type of sugar, namely: (cane sugar; palm sugar and coconut sugar) and varying the fermentation time 3;6;9;12 and 15) day. After obtaining the fermented coconut water kombucha drink, analysis was carried out to obtain the best coconut water kombucha. The tests carried out included lactic acid tests, Vitamin C levels, pH variance ANOVA tests kombucha was palm sugar type coconut water kombucha and a fermentation time of 15 days with a lactic acid content of 3.6302% and a Vitamin C content of 0.3052, pH 3.2 and the organoleptic test results had an average color, aroma , and taste of 3.1.